Penerapan Metodologi Rapid Application Development dalam Membangun Aplikasi TourGo untuk Mendukung Digitalisasi Pemesanan Tour Guide Wisata - Rohmawati, Aufa Ikrimah; Andriani, Anik; Meyliana, Anastasia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The demand for easily accessible, reliable, and informative tour guide services continues to increase along with the growth of the digital tourism industry. However, tourists still face various obstacles such as difficulty in finding professional tour guides, unclear prices, and the lack of a structured booking system. On the other hand, many tour guides do not yet have effective digital means to promote their services. This study aims to develop the TourGo application as a web-based platform that facilitates the process of searching and booking tour guides practically and safely. The method used is Rapid Application Development (RAD), which allows the development process to take place quickly through an iterative and prototyping approach. This application is designed with main features such as user registration, searching for tour guides by location and category, booking services, and a review and rating system. System testing was carried out using the black-box method and the calculation of the success rate on the tour guide interface showed a success rate of 95%, while the calculation of the success rate on the member interface showed a success rate of 91.67%, indicating a high level of user satisfaction. The results of the study indicate that the use of the RAD method is effective in producing applications that are in accordance with user needs and are able to answer problems in booking tour guides. The TourGo application is expected to be a digital solution that supports the development of technology-based tourism and increases the professionalism of local tour guide services.